CONAT 2016 International Congress of Automotive and Transport Engineering - Chiru, Anghel; Ispas, Nicolae (Springer International Publishing : Imprint: Springer, 2017)
The volume will include selected and reviewed papers from CONAT - International Congress of Automotive and Transport Engineering to be held in Brasov, Romania, in October 2016. Authors are experts from research, industry and universities coming from 14 countries worldwide. The papers are covering the latest developments in automotive vehicles and environment, advanced transport systems and road traffic, heavy and special vehicles, new materials, manufacturing technologies and logistics, accident research and analysis and innovative solutions for automotive vehicles. The conference will be organized by SIAR (Society of Automotive Engineers from Romania) in cooperation with FISITA. .